Net Fiscal Flows and the Size of Cities - Zimmermann, Horst (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Which regions contribute most to national growth? Do large cities ‘need’ more expenditure per capita? The relation between these two questions is the subject of a current German discussion, but it is of importance for other countries as well. What precisely is the issue? The substantial German fiscal equalization systems between states (Länder) and between communities assign estimates of higher expenditure need per capita to larger cities. This paper argues that this is justified, because, following the arguments of new regional economics, the modern agglomerations are of crucial importance for national growth. To maintain this role they have to be able to keep or receive enough public finance. To assess this, total public flows out of and into regions have to be taken into account. The relevant analysis shows that their contribution to upper-level (federal and Länder) finances is far above average, but that they receive relatively little from federal and Länder spending; consequently they experience large net fiscal outflows. The use of the abovementioned progressive scale of expenditure need in the equalization systems reduces this fiscal siphoning-off, at least to some extent.